SAT0340 CHARACTERIZATION OF PATIENTS WITH AXIAL SPONDYLOARTHRITIS BY PRESENCE OF ENTHESITIS: DATA FROM THE CORRONA PSORIATIC ARTHRITIS/SPONDYLOARTHRITIS (PSA/SPA) REGISTRY. (June 2019) - Mease, Philip J.; Liu, Mei; Rebello, Sabrina; Hua, Winnie; Mclean, Robert; Yi, Esther; Park, Yujin; Ogdie, Alexis
Abstract : Background: Enthesitis is a common extra-axial manifestation in patients with axial spondyloarthritis (AxSpA) 1, 2 ; however, not much is known about the prevalence of enthesitis in AxSpA and its impact on disease burden in US real-world settings. Objectives: This study describes characteristics of patients with AxSpA who had enthesitis vs patients without enthesitis. Methods: This study included patients aged ≥ 18 years with AxSpA enrolled in the Corrona PsA/SpA Registry between March 2013 and August 2018. Enthesitis at enrollment was assessed via the Spondyloarthritis Research Consortium of Canada (SPARCC) Enthesitis Index. Patient demographics, clinical characteristics, treatment profiles, disease activity, quality of life, and work productivity were compared between patients with and without enthesitis using t tests or Wilcoxon rank-sum tests for continuous variables and χ 2 or Fisher's exact tests for categorical variables. Results: Of 477 patients with AxSpA, 121 (25.4%) had enthesitis. Symptom and disease duration were similar between patients with and without enthesitis. In patients with enthesitis, a higher proportion were female, were more likely to have non-radiographic AxSpA and a history of depression, serious infections, and fibromyalgia vs those without enthesitis (all P < 0.05; Table 1 ). Current treatment with biologics or conventional synthetic disease-modifying antirheumatic drug (csDMARD) monotherapy was similar regardless of presence of enthesitis; however, patients with enthesitis were more likely to have prior csDMARD and biologic use, as well as current methotrexate use. Patients with enthesitis had worse disease activity (ASDAS, BASDAI, and BASFI scores; tender and swollen joint counts; physician global assessment; and DAPSA and cDAPSA scores), spinal mobility measures, quality of life (pain, fatigue, HAQ scores, and EQ VAS scores), and greater work impairment than patients without enthesitis (all P < 0.05; Table 2 ). Conclusion: Among patients with AxSpA in this US real-world study, the presence of enthesitis was associated with worse disease activity and quality of life compared to patients without enthesitis. References: [1] Nadon V, et al. Clin Exp Rheumatol. 2018Dec19 [Epub ahead of print]. [2] de Winter JJ, et al. Arthritis Res Ther. 2016;18(1):196. Acknowledgement: This study was sponsored by Corrona, LLC. Corrona is supported through contracted subscriptions with multiple pharmaceutical companies. The abstract was a collaborative effort between Corrona and Novartis, with financial support provided by Novartis. Disclosure of Interests: Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Mei Liu Employee of: M. Liu is an employee of Corrona, LLC., Sabrina Rebello Employee of: Corrona, LLC, Winnie Hua Employee of: W. Hua is an employee of Corrona, LLC., Robert McLean: None declared, Esther Yi Consultant for: E. Yi is a postdoctoral fellow at the University of Texas at Austin and Baylor Scott and White Health, providing services to Novartis Pharmaceuticals Corporation., Yujin Park Employee of: Y. Park is an employee of Novartis., Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda